Analisis Pengaruh Kualitas Produk, Promosi, dan Citra Merek terhadap Keputusan Pembelian Motor Merek Honda: Studi Kasus Mahasiswa Kelas Reguler di Universitas Indraprasta PGRI Jakarta - Tony Margiyanto Adi; Muzdalifah Muzdalifah; Askardiya Mirza Gayatri (Neolectura, 2022)
The development of the motorcycle business, especially in the country, has recently experienced a fairly high increase. Business competition in this field is automatically getting tougher. Purchasing decisions are an important element in maintaining and growing the company. The purpose of this study was to determine the effect of product quality, promotion and brand image on purchasing decisions for Honda motorcycles in regular class students, either partially or simultaneously. The method used is the analysis of validity and reliability, multiple linear regression equation, correlation, and hypothesis testing (t test and F test) and the coefficient of determination. The study population is classified into a limited population (finite), for a known amount of certainty, a population of about 500 respondents / students. Using the Slovin formula, a sample of 83 respondents was obtained. By using the computer assistance program SPSS for Windows 22.00, the equation of the multiple linear regression line is obtained as follows: Purchase Decision (Y) = 0.258 + 0.255 Product Quality + 0.238 Promotion + 0.598 Brand Image. The relationship between product quality and purchasing decisions is 0.586 quite strong and unidirectional, the relationship between promotions and purchasing decisions is 0.497 strong and unidirectional, and the relationship between brand image and purchasing decisions is 0.597, strong and unidirectional. From the results of the research, the coefficient of determination shows that product quality, promotion and brand image combined on the purchase decision of Honda brand motorcycles is 51.9% while the remaining 48.1% (100% - 51.9%) is influenced by other factors originating from outside this regression model. For example the perception of price, service quality, place or location and others.